Cooperation and conflict GDR theatre censorship, 1961-1989 - Bradley, Laura J. R. (Oxford University Press, 2010)
This study explores how theatre was censored in the GDR from 1961 to 1989. By examining a range of case studies, from banned stagings to those that met with official approval, it reveals the shifting patterns of cooperation and conflict that shaped the space for theatrical experimentation.